2000
DOI: 10.1006/viro.2000.0629
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Human Herpesvirus 8 in Africa: Both B and A5 K1 Genotypes, as Well as the M and P Genotypes of K14.1/K15 Loci, Are Frequent and Widespread

Abstract: We have studied 52 new HHV8 strains by sequencing the complete hypervariable K1 gene and genotyping the K14.1/K15 loci located at both sides, respectively, of the viral genome. The samples originated from 49 patients with Kaposi's sarcoma (KS; 32 patients), multicentric Castleman's disease (MCD; 12 patients), or primary effusion lymphoma (PEL; 5 patients). Among these patients, 32 were of African origin (West and Central African countries and Creoles from French Guiana) and the 17 others were mostly French hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
115
5
12

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(152 citation statements)
references
References 39 publications
16
115
5
12
Order By: Relevance
“…Indeed, the prevalence of subtype A5 in Zimbabwe (45%) is remarkably similar to that observed in smaller studies of other ethnic groups in diverse geographic areas in Africa: A5 was identified in 53% of 31 KS patients in Uganda (Kajumbula et al 2006) and 34% of 32 KS patients in West and Central African countries (Lacoste et al 2000). Zimbabwean A5 sequences in our study were closely related to each other and to reference sequences from distant areas of Africa with little evidence of genetic diversity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Indeed, the prevalence of subtype A5 in Zimbabwe (45%) is remarkably similar to that observed in smaller studies of other ethnic groups in diverse geographic areas in Africa: A5 was identified in 53% of 31 KS patients in Uganda (Kajumbula et al 2006) and 34% of 32 KS patients in West and Central African countries (Lacoste et al 2000). Zimbabwean A5 sequences in our study were closely related to each other and to reference sequences from distant areas of Africa with little evidence of genetic diversity.…”
Section: Discussionsupporting
confidence: 86%
“…Zimbabweans with AIDS-KS typically have advanced HIV-1 disease, KSHV viremia, high tumor burdens, and short survival (Campbell et al, 2003;Olweny et al, 2005). Much of what is known about K1 diversity in African populations comes from studies of persons with KS in East and Central Africa (Zong et al, 1999;Zong et al, 2002;Lacoste et al, 2000). Little is known about KSHV genetic diversity in Zimbabwe.…”
Section: Introductionmentioning
confidence: 99%
“…The TA cloning procedure, DNA sequencing, as well as the phylogenetic tree constructions using the PHYLIP package have been described previously (Lacoste et al 2000a(Lacoste et al , 2000c.…”
Section: Southern Blot Analysismentioning
confidence: 99%
“…KSHV infection has also been described in cases of haemophagocytic syndrome (HPS) but is not the only viral cause of this condition [15][16][17]. association with certain human populations can still be seen for clades B, D, and E, which are found primarily in people of African descent, old Asian and Polynesian populations, and Amerindian populations, respectively [30][31][32][33][34][35]. With the exception of a branch of clade A, A5, which is also frequently found in Africa [30,32], clades A and C are now found in northern Europe, the Americas, and Asia without any clear-cut association with defined populations, presumably as a result of the extensive mixing of European populations during the history of human migration.…”
Section: History and Involvement In Diseasementioning
confidence: 99%
“…However, one viral gene, K1, located at the 'left' end of the viral genome in the orientation shown in Figure 1, contains hypervariable regions with up to 40% protein sequence divergence between different clades [30][31][32][33][34][35]. Remarkably, the protein sequence in these hypervariable regions seems to have evolved as a result of some selective pressure [30,31,35].…”
Section: History and Involvement In Diseasementioning
confidence: 99%